Minimally Invasive Aesthetic Surgery Techniques Botulinum Toxin, Filler, and Thread Lifting - Lee, Won.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
In this book, authors will describe various techniques about botulinum toxin injection, filler injection and thread lifting based on latest evidences of minimally invasive plastic surgery techniques. For example, doppler ultrasound guided filler injection technique, short scar minimally invasive thread lifting techniques, and neck lifting techniques. Also described the basic knowledge for minimally invasive aesthetic techniques such as hyaluronic acid filler properties and rheology, threads components and classifications, and botulinum toxin classifications. Simple and easy techniques are described for beginners and also showed step by step injecting photographs. Also described basic anatomy for botulinum toxin, filler injection and thread lifting. Various detail illustrations and clinical photographs will be presented to help readers easier understanding and performing procedures. .
Chapter 1. Aesthetic aspect of minimal invasive technique -- Chapter 2. Anatomy for botulinum toxin -- Chapter 3. Botulinum toxin injection technique -- Chapter 4. Anatomy of filler injection -- Chapter 5. Properties of hyaluronic acid filler -- Chapter 6. Safe filler injection technique -- Chapter 7. Ultrasound guided filler injection -- Chapter 8. Filler complications -- Chapter 9. Anatomy for thread lifting -- Chapter 10. History of thread -- Chapter 11. Basic of thread -- Chapter 12. Thread lifting techniques -- Chapter 13. Thread rhinoplasty -- Chapter 14. Neck lifting by elastic thread -- Chapter 15. Neck countouring by liposuction and thread -- Chapter 16. Short scar rhytidectomy -- Chapter 17. Thread complications -- Chapter 18. Body contouring with thread and fat injection.
Keywords: Surgery, Plastic; Dermatology; Plastic Surgery; Dermatology; Plastic Surgery Procedures -- methods; Minimally Invasive Surgical Procedures -- methods; Botulinum Toxins, Type A -- therapeutic use; Dermal Fillers -- therapeutic use; Injections, Intradermal -- methods